Visualising Human Migrations in Cape Town The story of three ships through ‘time’, ‘space’ and ‘memory’ - Singh, Meghna (Department of Drama, 2020)
This practice-led PhD contributes to an understanding of contemporary art practice as a tool to render visible and unravel capitalist imaginaries within the field of migration studies. Focusing on the theme of contemporary and historical migrations at Cape Town through research conducted on three ships between 2013 and 2017, it uses the themes of ‘time’, ‘space’ and ‘memory’ to visualise migrations. The PhD interrogates the hidden process of globalisation; the invisibility of the workings of the port; the invisibility of the workers; their stories and their connection to the movement of capital, and renders them visible through the research. The study is situated at the intersection of migration studies, visual art practices and artistic research methods. Using the methodology of observational filmmaking and the creation of immersive multimedia installations incorporating virtual reality, it borrows from the work of anthropologists like David MacDougall (1998); Michael Taussig (1993); James Clifford (1988); Alyssa Grossman (2013); and Anna Grimshaw and Amanda Ravetz (2005) who make a case for the technique of ‘visualising anthropology’ in the field of ethnographic enquiry. Furthering the case of observational filming as a sensory form of investigation, I draw on the work of film scholar Laura Marks who advocates the phenomenon of “tactile epistemologies” (2000) and Doug Aitkens whose creations of split narrative videos illustrate the immersive experience I seek to achieve in my creative outputs. The central argument of this study is that an experience of research, conducted through the medium of observational filmmaking and presented via immersive video installations, creates visibility, empathy and an understanding of situations through corporeal embodiment, adding to the field of visual art and migration research.